1996
DOI: 10.3109/13625189609150680
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of compliance with oral contraception in Spain

Abstract: Strategies to improve compliance in Spain aim mainly at improving the general perception of the method and the accessibility of family planning centers. Factors associated with compliance are still not well known in our country. Better knowledge of the determinants of non-compliance in Spain is needed. For this purpose, another research group was formed to conduct a national study among women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“… 2 The high rates of UP in Spain might be related to the high use of SARC which, to be effective, need to be associated with user compliance. National surveys show a substantial rate of non-compliance affecting oral contraception, 22 and inconsistent use of condoms (20.0% of users), particularly by young people. 23 These two contraceptive methods are the most commonly used in Spain.…”
Section: Discussionmentioning
confidence: 99%
“… 2 The high rates of UP in Spain might be related to the high use of SARC which, to be effective, need to be associated with user compliance. National surveys show a substantial rate of non-compliance affecting oral contraception, 22 and inconsistent use of condoms (20.0% of users), particularly by young people. 23 These two contraceptive methods are the most commonly used in Spain.…”
Section: Discussionmentioning
confidence: 99%
“…Although a decrease in dose has been achieved together with a reduction in secondary effects, without any loss of effectiveness of the pill, there are still many women who are reluctant to use this type of birth control method. Studies have shown that in some developed countries (for example, Spain), only a small percentage of women of fertile age take OCs, and many of them do not take the pill on a regular basis 7,8 .…”
mentioning
confidence: 99%